Potential Impact of Dialysate Magnesium on Intradialytic Hypotension - Michael S Balzer; Janina Müller-Deile; Daniela I Schulze; Georg Eisenbach; Bernhard MW Schmidt; Hermann Haller; Roland Schmitt (Archives of Renal Diseases and Management - Peertechz Publications, 2016)
Numerous beneficial effects on cardiovascular health have been described for magnesium (Mg). Intradialytic hypotension (IDH) is a common complication in hemodialysis patients which contributes to cardiovascular mortality. It has been suggested that higher dialysate Mg (DMg) might reduce the risk of IDH. In this 24-month retrospective observational analysis we studied the incidence of IDH in 45 stable hemodialysis patients who underwent conversion from 0.5 mmol/L  DMg to 1.0 mmol/L. Mean serum Mg was 1.12 ± 0.03 mmol/L pre-conversion and changed to 1.35 ± 0.04 mmol/L post-conversion. In parallel, incidence of IDH showed a significant decrease from 1.59 ± 0.34 to 1.08 ±0.27 % comparing 12 months before and 12 months after DMg conversion. The incidence of muscle cramps and serum calcium showed a trend for reduction while other parameters were unchanged. In conclusion, switching patients from 0.5 mmol/L DMg to 1.0 mmol/L was associated with a significant improvement of IDH incidence without significant changes in other parameters that were analyzed in this study. Further studies are warranted to test the association between DMg and IDH in a prospective randomized fashion.